DEVELOPMENT OF STUDENTS' RELIGIOUS TOLERANCE THROUGH RELIGIOUS ACTIVITIES IN PUBLIC JUNIOR HIGH SCHOOL 17 MEDAN - Ayu, Melisa Gusti; Said, Naufal; Al Karim Rambe, Rahmansyah Fadlul (Pena Cendekia Insani, 2024)
The job of training in developing a demeanor of resilience among individuals is to depict a disposition of resistance in strict life among understudies. Strict variety is frequently expected to set off struggle inside a greater part bunch against a minority. In any case, the strict variety that is found in most of schools doesn't cause struggle in view of contrasts in strict foundations. The point is to recognize types of strict resistance in schools and examine educator systems in encouraging understudies' strict resilience. The execution of strict exercises with regards to shaping the personality of resilience among strict individuals, the personality of resistance between strict individuals is applied in the acts of other strict exercises that are felt to be viable. Since as well as giving the premise of strict lessons, understudies/understudies are likewise straightforwardly acquainted with genuine practice in building connections. correspondence with one another with different religions.